Terapêutica crónica em idosos numa Unidade de Saúde Familiar: análise da polimedicação e medicação potencialmente inapropriada - Souto, Márcia Mendonça (2018)
Introduction: The improvement of health care and socioeconomic conditions have contributed to an increased longevity of the population, which is associated with a higher prevalence of chronic diseases. This population often needs treatment by means of polypharmacy, which increases the risk of iatrogenic diseases. In elderly, drug interactions (DI) and exposure to the use of potentially inappropriate medication (PIM) can result in deleterious consequences for their health. Objectives: This study aimed to better understand the use of chronic therapy by elderly aged 75 years old and over, registered at a Family Health Unit in Braga, Portugal. Specifically, we aimed to determine the frequency of polypharmacy and use of potentially inappropriate medication, and to identify predisposing factors associated to these problems. Results: Amongst the 86 patients studied, 96.5% were chronic users of at least one medication. Twenty-four percent used 2-4 medications and 74.4% used five or more medications. In 37.7% of the patients, use of PIM was identified according to Beers criteria, with 90.7% of these cases exhibiting a ‘high’ degree of inadequacy. There was a statistical significant association between the number of medications used and PIM. These two variables were also statistically associated with ‘self-perception of health’, with ‘who prepares the medication’ and with ‘knowledge of the purpose of medication’. Discussion/Conclusion: Polypharmacy and PIM are extremely frequent amongst elderly aged 75 years or over, in the population studied. From the data obtained, the authors sought to have an understanding of the socioeconomic context associated with an increased risk, to help to inform a clinical strategy to reduce the risks of iatrogeny.